CLINICAL AND DIAGNOSTIC FEATURES OF COMBINED FACIAL INJURIES - Shukhrat A. Boymuradov (International Journal of Medical Sciences And Clinical Research, 2023)
One of the features of recent years is an intensive growth of traumatism among all categories of the population. Their causes are: technogenic catastrophes, natural disasters, road accidents, as well as military conflicts. In large cities, the large number of road accidents and industrial injuries is a major social and economic problem. It should be noted that among people under 40 years of age, traumatism ranks first as a cause of death. The result of epidemiologic analysis showed that combined trauma of the facial skeleton is noted in men. The complexity of injuries was associated with the combination of multiple fractures and the presence of rarely diagnosed craniocerebral injuries (CCI).